2017
DOI: 10.1111/dar.12640
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent non‐drinkers: Who are they? Social relations, school performance, lifestyle factors and health behaviours

Abstract: Non-drinkers presented more adaptive and healthier behaviours than their drinking peers, but it is difficult to determine whether their health benefits were related to their improved alcohol status or to the more general trend towards adaptation that occurred from 2004 to 2012 among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 25 publications
4
41
1
1
Order By: Relevance
“…De Looze et al's [3] analyses of HBSC-data on weekly drinking among [11][12][13][14][15] year-olds showed that the onset of the decline occurred later and was generally weaker in Eastern Europe than in other parts of Europe. From 2002 to 2010, the prevalence increased in one country (Croatia), fluctuated or remained stable in seven countries (Austria, Latvia, Portugal, Slovenia, Czechia, Ukraine, Slovenia) and decreased significantly in 20 countries.…”
Section: The Evidence Of Less Youth Drinkingmentioning
confidence: 99%
See 2 more Smart Citations
“…De Looze et al's [3] analyses of HBSC-data on weekly drinking among [11][12][13][14][15] year-olds showed that the onset of the decline occurred later and was generally weaker in Eastern Europe than in other parts of Europe. From 2002 to 2010, the prevalence increased in one country (Croatia), fluctuated or remained stable in seven countries (Austria, Latvia, Portugal, Slovenia, Czechia, Ukraine, Slovenia) and decreased significantly in 20 countries.…”
Section: The Evidence Of Less Youth Drinkingmentioning
confidence: 99%
“…Moreover, data from ESPAD show that the trend started earlier in Iceland than in other European countries [65]. National surveys of all Icelandic [14][15][16] year-olds provide additional evidence of a sizable and steady decline since the late 1990s [20,34].…”
Section: The Evidence Of Less Youth Drinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Non‐drinking may be self‐reinforcing—Larm et al . found that non‐drinkers were better off in several aspects when compared to drinkers; they were healthier, had less mental health problems and did better in school.…”
mentioning
confidence: 99%
“…The changes in youth drinking seem to have been concurrent with changes in parenting practices; six studies in this special issue identify increases in parental supervision and parents’ attitudes towards youth drinking becoming more restrictive . Larm et al .…”
mentioning
confidence: 99%